Conflict Management Of National Unity Board And Regional Politics Of North Sulawesi Province (Case Study Of Handling Conflict Between Community Organizations) In Bitung City, North Sulawesi Province) - Strawinsky Christian Jakson Pantow; Eko Budi Santoso; Ella Wargadinata (Jurnal Scientia, 2024)
This thesis is the result of research on Conflict Management of the North Sulawesi Provincial Kesbangpolda Agency with a case study of conflict handling between community organizations of the Muslim Solidarity Agency (BSM) and the Manguni Makasiouw traditional forces in Bitung City, North Sulawesi Province. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. Data analysis method with data reduction, data presentation and conclusion drawn.From the results of research and discussion, it can be concluded that the conflict management carried out is adequate. The causes of conflict can be known to be individual differences due to underage members who have unstable emotions, provocateurs who use diversity to pit people against each other, external influences (conflict between Israel and Palestine), and the use of social media that is not balanced with an understanding of the issues from outside. Then it can be seen that the obstacles are budget, human resources and science and technology, while the supporters are infrastructure, science and technology, regulations, political conditions, and a safe and controlled situation.Thus, the advice that can be given by the author is that the North Sulawesi Provincial Government, in this case the Kesbangpolda Agency of North Sulawesi Province, must be ready to maintain harmony between religious communities and between mass organizations by paying attention to the North Sulawesi motto “Sitou Timou Tumou Tou” by being able to utilize current science and technology in an effort to implement consensus through technology, sufficient budgeting to facilitate public understanding of the forms and impacts of conflict, prepare adequate human resources in preventing and handling conflicts, and pay attention to the membership of mass organizations that are still underage.